GAMBARAN KEJADIAN DEPRESI LANSIA DI PANTI WREDHA DHARMA BHAKTI SURAKARTA - Dewi Wulandari; Estiningtyas (Universitas Duta Bangsa Surakarta, 2020)
The elderly are very susceptible to health problems, including depression caused by stress in the face of life changes such as retirement, illness or physical disability, placement in nursing homes, partner deaths, and the need to care for couples whose health is declining. The purpose of this study was to determine the description of the incidence of depression in elderly at Dharma Bhakti Surakarta nursing homes. This research was descriptive research. The study was conducted in May - July 2019. The population of this research was the elderly who are in Dharma Bhakti Surakarta nursing homes. Sampling used total sampling and obtained a sample of 73 respondents. Data collection techniques were carried out through filling the Geriatric Depression Scale-30 questionnaire. The results showed that most of the elderly (65.8%) did not experience depression. As many as 30.1% of respondents experienced mild depression and 4.1% experienced severe depression. Most respondents who were depressed were aged 60-74 years (15 elderly), female (18 elderly), had a history of working as a laborer (9 elderly), not graduating from elementary school (13 elderly), being widowed (12 elderly), and has independent functional abilities (20 elderly). Conclusion: The incidence of depression in Surakarta Wedha Dharma Bhakti Orphanage reached 34% (as many as 25 elderly from 73 respondents).